A Case Report of Kussmaul-Maier Disease - O.O. Andrushkova; N.V. Malachkova; K.Iu. Grizhimalskaia; Ie.G. Manko; T.M. Zhmud (Ukrainian Society of Ophthalmologists, 2019)
Background: Kussmaul-Maier disease (also known as polyarteritis nodosa or PAN) is a systemic disorder characterized by destructive and proliferative changes in the walls of arteries (mainly muscular arteries and arterioles). Purpose: To present a case exemplifying the ocular manifestations of Kussmaul-Maier disease. Materials and Methods: The patient underwent visual acuity assessment, tonometry, and comprehensive eye examination. In addition, she underwent brain MRI and duplex sonography of the major arteries supplying the head. Results and conclusion: This case demonstrates the features of disease course and ophthalmologist's tactics in the treatment of Kussmaul-Maier disease. Kussmaul-Maier disease has a recurrent course with long-lasting (as long as 11 years) periods of remission and favorable visual prognosis.